Experimental investigation of ignition mode and performance of the annular combustor. (15th November 2022) - Li, Wei; Wang, Yibo; Liu, Yunpeng; Yan, Yingwen
Highlights: Ignition performance of combustors with different head structures are investigated. The ignition performance envelope of an annular combustor is further improved. Four ignition patterns of combustible mixture at the outlet of swirler are summarized. The changes of time parameters during ignition are statistically and quantitatively analyzed. Abstract: This study examined the ignition performance of a triple-dome sector combustor via experiments. For this, the self-radiation flame image in the dynamic ignition process taken by the high-speed camera was processed, and the results were analyzed. The experimental results obtained are given as follows: 1) Based on ignition performance, the ignition performance envelope of an annular combustor is mainly divided into unburnt zone, nonpropagating zone, and ignition success zone; 2) Based on dynamic flame image processing and analysis, four ignition patterns of combustible mixture at the outlet of swirler are summarized in the combustor with high-temperature hot jet flame as ignition mode; 3) The changes of time parameters in the ignition process are obtained through image processing. It is found that in the successful ignition zone, the growth time of swirling flame and ignition time decrease with the increase in fuel–air-ratio; 4) The effects of the head structure parameters on the ignition performance and flame circumferential propagating time of the combustor are analyzed. This study also summarized several typical combustor ignition modes in the triple-dome sector combustor and improved the ignition performance envelope of the annular combustor.